Risk Factors for Chronic Cough in Young Children: A Cohort Study - Au-Yeung, Yin To; Chang, Anne B.; Grimwood, Keith; Lovie-Toon, Yolanda; Kaus, Michelle; Rablin, Sheree; Arnold, Dan; Roberts, Jack; Parfitt, Sarah; Anderson, Jennie; Toombs, Maree; O'Grady, Kerry-Ann F. (Frontiers in Pediatrics, 2020)
Background: Data on the predictors of chronic cough development in young children are scarce. Our primary objective was to examine the factors associated with young children developing a chronic cough, with a focus on childcare attendance. Methods A secondary analysis of data collected in a prospective cohort study of children presenting to three emergency departments and three primary healthcare centres in southeast Queensland, Australia. Eligible children where those aged <6-years presenting with cough and without known underlying chronic lung disease other than asthma. Children were followed for 4 weeks to ascertain cough duration. The primary outcome was persistent cough at Day-28. Multinomial regression models were undertaken to identify independent predictors of chronic cough. Results: In 362 children, 95 (26.2%) were classified as having chronic cough. Gestational age (adjusted relative risk (aRR)=3.5, 95% confidence interval (CI) 1.4-8.8), underlying medical conditions (aRR=2.7, 95%CI 1.3-5.7), a history of wheeze (aRR=2.6, 95%CI 1.4-4.8) and childcare attendance (aRR=2.0, 95%CI 1.1-3.8) were independent predictors of chronic cough. Amongst childcare attendees only, 64 (29.8%) had chronic cough at day-28. The strongest predictor of chronic cough amongst childcare attendees was continued attendance at childcare during their illness (aRR=9.3, 95%CI 1.8-49.0). Conclusion: Gestational age, underlying medical conditions, prior wheeze and childcare attendance are risk factors for chronic cough in young children. Parents/carers need to be aware of the risks associated with their child continuing to attend childcare whilst unwell and childcare centres should reinforce prevention measures in their facilities.